Alevis in Europe (London ; New York)
xxx, 252 sayfa
Keywords: “The Alevis are a significant minority in Turkey, and now also in the countries of Western Europe. Over the past century, many of them have migrated from rural enclaves on the Anatolian plateau to the great cities of Istanbul and Ankara, and from there to the countries of the European Union. This book asks who are they? How do they construct their identities – now and in the past; in Turkey and in Europe? A range of scholars, writing from sociological, historical, socio-psychological and political perspectives, present analysis and research that shows the Alevi communities grouping and regrouping, defining and redefining – sometimes as an ethnic minority, sometimes as religious groups, sometimes around a political philosophy - contingently responding to circumstances of the Turkish Republic’s political position and to the immigration policies of Western Europe. Contributors consider Alevi roots and cultural practices in their villages of origin; the changes in identity following the migration to the gecekondu shanty towns surrounding the cities of Turkey; the changes consequent on their second diaspora to Germany, the UK, Sweden and other European countries; and the implications of European citizenship for their identity. This collection offers a new and significant contribution to the study of migration and minorities in the wider European context“ -- Yayıncı.